2016
DOI: 10.1002/pmic.201500546
|View full text |Cite
|
Sign up to set email alerts
|

Revealing oxidative damage to enzymes of carbohydrate metabolism in yeast: An integration of 2D DIGE, quantitative proteomics, and bioinformatics

Abstract: Clinical usage of lidocaine, a pro-oxidant has been linked with severe, mostly neurological complications. The mechanism(s) causing these complications is independent of the blockade of voltage-gated sodium channels. The budding yeast Saccharomyces cerevisiae lacks voltage-gated sodium channels, thus provides an ideal system to investigate lidocaine-induced protein and pathway alterations. Whole-proteome alterations leading to these complications have not been identified. To address this, S. cerevisiae was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…It is a metalloenzyme involved in the catalysis of 2-phosphoglycerate to phosphoenolpyruvate in the penultimate step of glycolysis [62]. Manaa et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is a metalloenzyme involved in the catalysis of 2-phosphoglycerate to phosphoenolpyruvate in the penultimate step of glycolysis [62]. Manaa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cell vitality was assessed using FungaLight 5-carboxyfluorescein diacetate, acetoxymethyl ester (CFDA,AM)/Propidium Iodide (PI) Yeast Vitality Kit (Life Technologies) according to the manufacturer’s protocol. Protocol and LC 50 concentrations were reported in previous published manuscript [16] . Briefly, volume of culture equivalent to 10 6 cells was collected and exposed to a range of lidocaine concentrations (5-30 mM), hydrogen peroxide concentrations (1-20 mM), and vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies assessing lidocaine toxicity using rat dorsal root ganglion neurons reported superoxide generation, mitochondrial depolarization, intracellular alkalization, and phosphatidylserine externalization [13] . Characteristically, oxidative stress causes protein carbonylation that frequently reduces protein activity [14] , [15] , [16] . In prior examination of lidocaine toxicity in S. cerevisiae we have shown carbonylation to multiple proteins involved in carbohydrate metabolism and general bioenergetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations